Correction: Risk Factors of Streptococcus suis Infection in Vietnam. A Case-Control Study. - Ho, D; Le, T; Wolbers, M; Cao, Q; Nguyen, V; Tran, V; Le, T; Nguyen, H; Tran, T; Dinh, X; To, S; Hoang, T; et al. (Public Library of Science, 2011)
[This corrects the article on p. e17604 in vol. 6.].